WHAT AUSTRIAN INVESTING IS NOT (AND WHAT IT IS): A REVIEW AND SUGGESTED WAY FORWARD - APP, DAVID J. R; OLBRICH, MICHAEL; DAHER, TREVOR; MA AS, ALEX ANDER (REVISTA PROCESOS DE MERCADO, 2025)
Various attempts have been made to develop an applied Austrian investment theory or a practical investment framework that is either consistent with or directly derived from the general corpus of Austrian economic theory. This article will first provide a sum- mary review of existing research in this area, both in popular books and in scholarly journal articles, without claiming to be exhaustive. In its review, this article will offer the gentle criticism that much of this existing research has ignored core Austrian insights and principles, rendering the proposed approaches ulti- mately incompatible with Austrian economics. Some Austrians have embraced the value investing framework of Columbia Business School and Wall Street fame, having recog- nized some parallels between value investing and Austrian eco- nomic theory (e.g., Leithner, 2017; Taghizadegan et al., 2016). Others have recommended, more generally, that practitioners make capi- tal investments in diversified portfolios (Skousen, 2013), with the caveat that this should be done in jurisdictions with “free markets and free trade” (Skousen, 2013, p. 24), offering the insight that these